Development of a School-Based Restorative Practices Training for Parents: Impacts on Parent and Child Outcomes - Hughes, Christopher R (2018)
Restorative Practices (RP), a science of proactively building trusting and mutual relationships, is an effective framework focused on three key features of positive student discipline: building behavioral competence, addressing negative behavior, and fostering school climate. While educators are trained to use RP preventatively and reactively, parents are often only given information to use RP reactively. Strategies for proactively inviting parents to learn about and utilize RP at home are necessary to foster homeschool consistency regarding preventative discipline strategies. For the present study, 11 parents volunteered to participate in a preliminary school-based parent training designed to elicit critical parent outcomes: knowledge of RP principles/strategies, parent selfefficacy to use RP, and social validity of RP as an approach to discipline. Hypotheses for increases in parent-reported child outcomes around relationship skills and decisionmaking skills for their children between the ages of eight to twelve-years-old were also made. Using a quasi-experimental design, pre-post intervention effects on a treatment group were compared to a nonequivalent control group. Results indicated the treatment group of parents acquired greater RP knowledge, they perceived greater self-efficacy to use RP, and they validated RP as a useful discipline approach they wanted to use after attending the RP parent training. They also reported greater parent-perceived child relationship skills and decision-making skills. Implications on school-based RP implementation, the use of RP as a primary prevention tool and strategies for fostering shared accountability for child outcomes using RP will be discussed